2021
DOI: 10.1186/s41983-020-00266-0
|View full text |Cite
|
Sign up to set email alerts
|

Anosmia and COVID-19: perspectives on its association and the pathophysiological mechanisms involved

Abstract: With the spread of SARS-CoV-2, contingency measures and plans to facilitate the screening of infected patients are needed. Changes in olfaction have been cited as symptoms of the disease, and it is important to prove or exclude its association with this condition to refine the symptomatic criteria for early isolation. This article aims to analyze the association between olfactory disorders and SARS-CoV-2 infection as well as investigate the possible underlying pathophysiological mechanisms. The research was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 34 publications
(39 reference statements)
0
20
0
5
Order By: Relevance
“… 48 ACE-2 receptors are highly expressed in the nasal cavity and olfactory bulb, and this can be the potential pathway for olfactory dysfunction as SARS-CoV-2 has a greater affinity toward the ACE-2 receptor. 49 Olfactory dysfunction can be a prognostic marker for the prediction of severity of disease as persistent olfactory dysfunction at 20 days is associated with disease severity. 50 Olfactory dysfunctions are often reported together with gustatory dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“… 48 ACE-2 receptors are highly expressed in the nasal cavity and olfactory bulb, and this can be the potential pathway for olfactory dysfunction as SARS-CoV-2 has a greater affinity toward the ACE-2 receptor. 49 Olfactory dysfunction can be a prognostic marker for the prediction of severity of disease as persistent olfactory dysfunction at 20 days is associated with disease severity. 50 Olfactory dysfunctions are often reported together with gustatory dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the first studies from China 10 , anosmia was mentioned to affect only about 5.1% of COVID-19 patients. Another study from France reported 47% patients with confirmed COVID-19 had anosmia 11 . The pathophysiological mechanism underlying the occurrence of anosmia is still not wellunderstood, but two explanations have been proposed 12 .…”
Section: Table-v Distribution Of Factors Associated With In Hospital Outcome Of Study Population (N=769)mentioning
confidence: 96%
“…SARS-CoV-2 not only involves lung, but may also affect the cardiovascular system [4][5][6] , gastrointestinal system 7,8 , central nervous system [9][10][11] , renal system 12 and skin 13 . The SARS-CoV-2 protein characteristic spike binds to its cellular receptor, the angiotensin-converting enzyme 2 (ACE2), which is widely expressed in many cell types and organs like lung alveolar cells, nasal epithelium, cerebral cortex, digestive tract, kidney, gallbladder, testis, and adrenal gland 11 . The majority of patients with COVID-19 infection are thought to be paucisymptomatic and do not require hospitalization 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with anosmia sometimes do not realize that they are sick. A meta-analysis article by Purja et al (2021) said that patients with anosmia had a low chance of being hospitalized. In the study of Klopfenstein et al Of the 114 COVID-19 patients, 54 (47%) patients experienced anosmia.…”
Section: Anosmia Associated With Lower Hospital Mortalitymentioning
confidence: 99%